Eye The Scientific Journal of The Royal College of Ophthalmologists - Sivaprasad, Sobha; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Springer Nature.)
Eye is the official journal of The Royal College of Ophthalmologists. It aims to provide the practising ophthalmologist with information on the latest clinical and laboratory based research. Whilst principally aimed at the practising clinician, the journal contains material of interest to a wider readership including optometrists, orthopists, other health care professionals and research workers in all aspects of the field of visual science.
Keywords: Laboratory medicine; Pharmaceutical technology; Medicine; Ophthalmology; Surgery; Surgical oncology; Medicine/Public Health, general; Ophthalmology; Laboratory Medicine; Surgery; Surgical Oncology; Pharmaceutical Sciences/Technology.